Data analytics for cybersecurity - Janeja, Vandana P., 1976- (Cambridge ; New York, NY : Cambridge University Press, 2022)
As the world becomes increasingly connected, it is also more exposed to a myriad of cyber threats. We need to use multiple types of tools and techniques to learn and understand the evolving threat landscape. Data is a common thread linking various types of devices and end users. Analyzing data across different segments of cybersecurity domains, particularly data generated during cyber-attacks, can help us understand threats better, prevent future cyber-attacks, and provide insights into the evolving cyber threat landscape. This book takes a data oriented approach to studying cyber threats, showing in depth how traditional methods such as anomaly detection can be extended using data analytics and also applies data analytics to non-traditional views of cybersecurity, such as multi domain analysis, time series and spatial data analysis, and human-centered cybersecurity.
Introduction - data analytics for cybersecurity -- Understanding sources of cybersecurity data -- Introduction to data mining : clustering, classification and association rule mining -- Big data analytics and its need for cybersecurity -- Types of cyber attacks -- Anomaly detection for cyber security -- Anomaly detection -- Cybersecurity through time series and spatial data -- Cybersecurity through network and graph data -- Human centered data analytics for cyber security -- Future directions in data analytics for cybersecurity.
Title from publisher's bibliographic system (viewed on 10 Aug 2022).
Keywords: Computer security -- Data processing; Data mining